2007
DOI: 10.1094/phyto-97-11-1458
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Diagnosis of QoI Resistance in Cucumber and Eggplant Fungal Pathogens

Abstract: The molecular mechanism of QoI fungicide resistance was studied using isolates of cucumber Corynespora leaf spot fungus (Corynespora cassiicola) and the eggplant leaf mold (Mycovellosiella nattrassii). In both pathogens, a mutation at position 143 from glycine to alanine (G143A) was detected in the cytochrome b gene that encodes for the fungicide-targeted protein. Moreover, the nucleotide sequence at amino acid position 143 was converted from GGT or GGA in sensitive (wild-type) to GCT or GCA in resistant (muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 25 publications
3
74
0
2
Order By: Relevance
“…Such changes could include typical mechanisms that lead to fungicide resistance, such as the movement of transposable elements into the promoter region of a target gene (Luo and Schnabel, 2008b;Ma et al, 2006) or the implementation of nucleotide sequence variations in target genes (Ishii et al, 2007;Leroux et al, 2007). The purpose of this study was to investigate whether fungicide stress can lead to genetic changes typically associated with fungicide resistance in a phytopathogenic, filamentous fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes could include typical mechanisms that lead to fungicide resistance, such as the movement of transposable elements into the promoter region of a target gene (Luo and Schnabel, 2008b;Ma et al, 2006) or the implementation of nucleotide sequence variations in target genes (Ishii et al, 2007;Leroux et al, 2007). The purpose of this study was to investigate whether fungicide stress can lead to genetic changes typically associated with fungicide resistance in a phytopathogenic, filamentous fungus.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study by Lesniak et al (2011), found ninety-eight percent of QoIresistant/shifted isolates screened in Michigan were associated with G143A, consistent with other phytopathogenic fungi resistant to this class of fungicides (Ishii et al, 2009;Ishii et al 2007). Sequencing the entire CYTb gene of resistant isolates that did not test positive for the G143A transition did not reveal other mutations in the structural gene, and suggests other mechanisms of resistance (Lesniak et al 2011).…”
Section: Qoi-the Quinone Outside Inhibitorsmentioning
confidence: 67%
“…1) binds with a hydrogen bond to the amide group of glutamic acid at position 272 in domain C; therefore, this region plays an important role in accepting fungicides. Since substitution of glycine for alanine at position 143 (G143A) in domain B significantly lowers the affinity of strobilurin fungicides to cytochrome b, 7,8,13,14,[19][20][21][22][23] interaction between domain B and strobilurin fungicides must be strong. On the other hand, substitution of phenylalanine for leucine at position 129 (F129L) in domain A has been shown not to significantly lower the affinity of strobilurin fungicides to cytochrome b.…”
Section: Discussionmentioning
confidence: 99%
“…These strains have been elucidated to have a substitution of glycine for alanine at position 143 (G143A mutation) in cytochrome b. 5,8) Fischer rats F344/DuCrlCrlj (Rattus norvegicus) and carp (Cyprinus carpio) were obtained from Charles River Laboratories Japan Inc. (Kanagawa, Japan) and Kato Koi Farm Company (Gifu, Japan), respectively. Etiolated seedlings of crops [cucumber (Cucumis sativus L.), tomato (Lycopersicon esculentum Mill.…”
Section: Methodsmentioning
confidence: 99%